Permanent urethral ligation after AUS cuff erosion: Is it ready for prime time?. Issue 1 (9th October 2020) - Van Dyke, Maia; Ortiz, Nicolas; Baumgarten, Adam; Ward, Ellen; Baker, Ryan; Hudak, Steven; Morey, Allen
Abstract: Aims: Although artificial urinary sphincter (AUS) has long been the gold standard treatment for severe stress urinary incontinence, poor tissue quality in patients with prior cuff erosions may preclude this option. Formal supravesical diversion and/or bladder neck closure comprise alternative salvage options but are associated with significant morbidity and mortality. We review our experience with permanent urethral ligation (PUL) among patients deemed not to be candidates for AUS replacement following cuff erosion. Methods: From a single‐center database of 396 patients undergoing AUS from 2014 to 2020, 20 men underwent PUL with suprapubic tube (SPT) diversion. Clinical characteristics and outcomes were evaluated. Quality of life (QOL) was assessed using chart review, Michigan Incontinence Symptom Index (M‐ISI), and Patient Global Impression of Improvement (PGI‐I). Results: PUL resulted in continence in 18 (90%) men; 15 after the initial surgery and three after repeat ligation. Patients were elderly (average age 75) with significant comorbidities. A total of 11 (55.5%) patients experienced complications in the 90‐day postoperative period (seven Clavien‐Dindo Grade II, four Grade III). Over an average follow‐up of 30.3 months (interquartile range: 15.75–48.75), four patients underwent cystectomy and one underwent perineal urethrostomy. In the remaining patients managed by PUL, 13 had satisfactory M‐ISI scores and indicated overall improvement on PGI‐I. Conclusions: For men with AUS cuff erosion who are poor candidates for replacement, PUL with chronic SPT drainage represents an acceptable alternative option to restore continence and improve QOL. Though complications are not uncommon, the morbidity profile still compares favorably to more invasive formal urinary diversion.